2018
DOI: 10.7573/dic.212531
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy in the treatment of hypertension

Abstract: Hypertension is a major preventable risk factor for atherosclerosis and ischemic heart disease. Although modern and effective antihypertensive drugs are available, most patients remain with a suboptimal blood pressure control. Most hypertensive patients will need a combination of antihypertensive agents to achieve the therapeutic goals – recent guidelines recommend initiating treatment with two drugs in those patients with a systolic blood pressure >20 mmHg and/or a diastolic blood pressure >10 mmHg above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 50 publications
2
102
0
7
Order By: Relevance
“…The hypertension treatment regimen in the current study showed that telmisartan and telmisartan-based combinations were the preferred choices of antihypertensive therapy in 64% of patients, followed by olmesartan and its combination in 11% of patients. These results were in concordance with Guerrero-García C et al who stated that in hypertensive diabetes patients, multiple drug therapy is necessary to achieve blood pressure targets [ 9 ]. Studies report the CV protection of metformin, as it reduces the risk factors of CV diseases, including lipids, overweight, and hypertension; thus, lowering the incidence of CVD [ 10 - 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…The hypertension treatment regimen in the current study showed that telmisartan and telmisartan-based combinations were the preferred choices of antihypertensive therapy in 64% of patients, followed by olmesartan and its combination in 11% of patients. These results were in concordance with Guerrero-García C et al who stated that in hypertensive diabetes patients, multiple drug therapy is necessary to achieve blood pressure targets [ 9 ]. Studies report the CV protection of metformin, as it reduces the risk factors of CV diseases, including lipids, overweight, and hypertension; thus, lowering the incidence of CVD [ 10 - 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the last couple of decades, combinational therapy has emerged as a promising strategy for treating several diseases such as cancer [ 5 , 6 ], diabetes [ 7 ], AIDS [ 8 ], hypertension [ 9 ], autoimmune diseases [ 6 ], tuberculosis [ 10 ], infectious diseases [ 11 , 12 ] and even against the recent COVID-19 pandemic [ 13 ]. In context to drug-resistance, ‘drug cocktails’ could be a game-changer as they come with several benefits such as (1) a broadened antimicrobial spectrum, (2) the likelihood of developing drug resistance would reduce substantially as the chances of acquiring resistance towards a novel combination would be much lower, (3) it could be more efficacious against polymicrobial infections, (4) if the exercised drugs act synergistically, i.e., the combined effect of antimicrobial agents used is greater than the sum of their individual effects, it could provide even better pathogen clearance than the single drug alone and that too at a very low concentration, and (5) the lower concentration of antimicrobial agents could minimize the drug toxicity in the host [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[12] There is evidence that BP control is poor when using monotherapy and that a minimum of two agents is usually required to reach target BP in the majority of patients. [27]…”
Section: Introductionmentioning
confidence: 99%